Keefektifan Kalimat dalam Teks Eksplanasi Siswa Kelas XI SMAN 13 Padang - Wilda Syahfitri (Universitas Negeri Padang, 2021)
There are five objectives of this research. First, describe the effectiveness of the sentence in terms of sentence structure. Second, describe the effectiveness of the sentence in terms of logical meaning. The third describes the effectiveness of the sentence in terms of word standard. Fourth, describe the sentence in terms of word savings. Fifth, describe sentences in terms of spelling accuracy. This type of research is qualitative with descriptive method. The data in this study are sentences in the explanatory text of class XI students of SMAN 13 Padang. Furthermore, the data sources in this study were twenty-five student assignments in writing explanatory texts for class XI SMAN 13 Padang in the 2020/2021 school year. The research instrument is the researcher himself. The data validation technique used in this research is triangulation technique. There are five results of this study. First, the effectiveness of the sentence in terms of structural clarity, there are 48 wrongs. Second, the effectiveness of the sentence in terms of logical meaning, there are 68 wrongs. Third, the effectiveness of the sentence in terms of the standard of words there are 73 wrongs. Fourth, the effectiveness of the sentence in terms of word savings contained 115 wrongs. Fifth, the effectiveness of the sentence in terms of the use of spelling which includes the use of capital letters, punctuation periods, and commas, there are 57 wrongs. Based on the results of the research, it can be concluded that the effectiveness of the sentences in the explanatory text of the XI grade students of SMAN 13 Padang is in poor qualification. This is evidenced by the 234 sentences found in this study, only 76 sentences were effective, while 158 sentences were ineffective. Kata Kunci : Kalimat Efektif, Teks Eksplanasi, Siswa